Potential of Exserohilum Longirostratum Bioherbicide for Rottboellia Cochinchinensis - Ahmad, Azean (2004)
Development of Exserohilum longirostratum as a potential bioherbicide for controlling itchgrass (Rottboellia cochinchinensis) was investigated in ths study. An isolate of inhgenous fungus E. longirostratum was isolated from diseased R cochinchinensis in Serdang, Selangor and was evaluated in the laboratory and greenhouse as a potential bioherbicide. Ths fungus was found to be hghly pathogenic to R cochinchinensis when the seedlings were inoculated with 3.5 X 10' conididml. The disease symptom appeared 24 h after inoculation as Qscrete eyespot symptoms with watery dark border, which was eventually associated with extensive necrosis on the leaves. The lesions did not coalesce, but the leaves and entire plants turned completely necrotic and died. The fungus grew and sporulated well on Potato dextrose agar (PDA) and V8 agar with optimum temperature for growth of 28°C. Although most of Exserohilum spp were reported as host to member of Poaceae, but E.longirostratum has a narrow host range, which include several weedy grass. Corn, rice and sugarcane showed resistant reaction while dicots were immune. The pathogen penetrated plant surfaces by direct penetration through formation of appressoria on surfaces of R. cochinchinensis 8 h post inoculation. The appresorium being usually bulbous or cylindrical often ends with the formation of extensive secondary hyphae. The fungus penetrated the cuticle cell wall and grew intra and intercellularly within the tissues. Extensive secondary hyhpae were produced within 32 h on R. cochinchinensis leaves, thus indicating that the fungus was able to establish parasitic relationship with the host. On corn leaves, the fungus grew and penetrate the leaf surface. The fungus did not produce extensive hyphae in corn tissue but were compartmentalized at the point of infection indicating resistant reaction. The fungus grew on bean leaves but could not penetrate the cell wall on bean as indicated by lysing of the conidia and germs tubes 8 h post inoculation. The inability of the germinating conidia to penetrate and to progress indicated that bean is not a compatible host for this fungus. The level of disease severity on R. cochinchinensis was linearly related to the conidial concentration of E. longirostratum with conidia concentration higher than lo4 conidia per mililiter resulted in 100% control of the seedlings. The most susceptible age of R. cochinchinensis were 2- to 8- leaf stage. E. longirostratum, required a minimum of 8 h of dew to infect R. cochinchinensis. Such long dew duration could be constraint to the use of this bioherbicide in the field. However, this constraint may be circumvented by adding amendments to the formulation. Thus, the potential of E. longirostratum to be used as a bioherbicide to control R. cochinchinensis was demonstrated.